Papua New Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper explores the medium-term determinants of the current account balance in Papua New Guinea. It provides an assessment of the exchange rate, and presents some background on recent exchange rate developments. It uses two dynamic panel regression models to estimate the current account and exchange rate determinants across 55 countries. The paper applies the estimation results to Papua New Guinea's data and presents the exchange rate assessment for the kina under a baseline scenario and a terms-of-trade-shock scenario.